Peningkatan Cakupan Indoor dengan Femtocell dalam Jaringan 5G pada Frekuensi 3500 MHz Menggunakan Radiowave Propagation Simulator - Desi Rianti; Muntaqo Alfin Amanaf; Alfin Hikmaturokhman; Ade Wahyudin (Journal of Information Technology and Its Utilization, 2024)
In the landscape of 5G mobile networks in Indonesia, one of the prominent frequency candidates is 3.5 GHz. The frequency is anticipated to be the initial choice for operators to deploy 5G networks. The research focuses on designing an indoor cellular network to address indoor network degradation issues using Small Cells, specifically Femtocells, within buildings such as schools, companies, hospitals, and airports. The design is implemented at PT. Sutanto Arifchandra Electronic (PT. SAE) based on the COST 231 Multi-Wall Propagation model using the Radiowave Propagation Simulator (RPS) 5.4 application. The required parameters for designing the indoor cellular network include residential building specifications and a Link Budget parameter to determine the number of Femtocell Access Points needed to cover all areas adequately. The coverage calculations determined that 2 Femtocell Access Points are required. The simulation uses three scenarios, with the optimal outcome observed in scenario 2 (employing 2 Femtocell Access Points positioned on the middle right and left sides of the walls). This scenario yields a signal power level of -25.60 dBm and a Signal to Interference Ratio (SIR) of 14.80 dB.